(untitled) (Economics and region, 2025)
The article examines the features and problems of using distance learning in teaching marketing cycle disciplines. Informatization of the educational process is one of the important directions in the education reform of Ukraine. However, solving this problem creates challenges for interaction between participants in the distance process. The success of using information technologies in the educational process largely depends on how effectively modern psychological and pedagogical technologies are implemented, which are able to satisfy the educational needs of the individual. To highlight the problems of distance learning and find ways to overcome them, a marketing study was conducted. A questionnaire was developed for the study, which includes 6 questions. The sample size of respondents is 84 students of the "Marketing" specialty, including: 25 first-year students, 30 second-year students, 14 third-year students, and 15 fourth-year students.